Presence of Thyroid-Stimulating Hormone Receptor Antibodies in a Patient with Subacute Thyroiditis followed by Hypothyroidism and Later Graves' Disease with Ophthalmopathy: A Case Report - Hallengren, Bengt (Eur Thyroid J, 2015)
BACKGROUND: The development of Graves' disease (GD) after subacute thyroiditis (SAT) is very rare and only a limited number of cases have been reported. OBJECTIVES: Here, we report a patient with SAT followed by hypothyroidism and later GD, with ophthalmopathy, occurring 11 years after SAT. CONCLUSION: This case illustrates the appearance of thyroid-stimulating hormone (TSH) receptor antibodies in a female 1 year after SAT, the development of hypothyroidism requiring thyroxine, and later the occurrence of GD with severe ophthalmopathy, 11 years after SAT. The occurrence of SAT and GD may be coincidental but SAT may have induced the appearance of TSH-receptor antibodies, with the bioactivity changing from blocking, leading to hypothyroidism, and later to a stimulating activity that led to GD in a genetically susceptible patient.